Post-conflict ethics, archaeology and archaeological heritage: a call for discussion. (23rd December 2022) - Newson, Paul; Young, Ruth
Abstract: Ethics are fundamentally important to all forms of archaeological theory and practice and are embedded within many professional codes of conduct. The ethics of archaeological engagement with conflicts around the world have also been subject to scrutiny and debate. While archaeology and archaeological heritage are increasingly viewed as significant elements of post-conflict work, with much to contribute to rebuilding stable and secure societies, there has been limited acknowledgement and debate of post-conflict ethical issues and challenges for archaeologists. This paper is intended to stimulate discussion around major ethical issues, the problems and possible ways forward for post-conflict archaeology and archaeological heritage.